The implications for teaching and learning in Key Stage 1 as a result of the Covid-19 pandemic - Ayesha Lohar; Cathal O'Siochru (Educational Futures, 2023)
In this paper we will argue that as part of their plans to phase out the Key Stage 1 SATs (DfE, 2020), the government should consult with teachers to assess and evaluate the gaps in learning that have occurred and continue to occur in England as a result of the Covid-19 pandemic. Moreover, we hope to show that the pandemic has provided the perfect opportunity for the Department for Education (DfE) to utilise the research available on children’s development with specific reference to the socio-cognitive context in order to redefine the attainment targets so that they better align with childhood development trajectories. Finally, we intend to show that the DfE should be considering the potential impact of digital devices on children’s learning, as these have been used as a substitute for live lessons and can be used by parents and children to boost learning.